2020
DOI: 10.1074/jbc.ra120.015249
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine prevents binding of SARS–CoV-2 spike to its cellular receptor ACE2

Abstract: Sphingosine has been shown to prevent and eliminate bacterial infections of the respiratory tract, but it is unknown whether sphingosine can be also employed to prevent viral infections. To test this hypothesis, we analyzed whether sphingosine regulates the infection of cultured and freshly isolated ex vivohuman epithelial cells with pseudoviral particles expressing SARS-CoV-2 spike (pp-VSV-SARS-CoV-2 spike) that served as a bona fide system mimicking SARS-CoV-2 infection. We demonstrate that exogenously appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 30 publications
1
49
0
1
Order By: Relevance
“…We have previously shown that sphingosine also inhibits infection of human cells with SARS-CoV-2 ( 23 ). We therefore tested whether ambroxol alters cellular sphingosine concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that sphingosine also inhibits infection of human cells with SARS-CoV-2 ( 23 ). We therefore tested whether ambroxol alters cellular sphingosine concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…The S proteins of SARS-CoV and SARS-CoV-2 show organizational homology and preserved ectodomains, so that previous approaches are applied to stop binding of SARS-CoV to its host cell receptor, angiotensin-converting enzyme 2 (ACE2) through a non-pH dependent endocytosis, since SARS-CoV-2 also employs ACE2 for cell entry[ 5 , 6 ]. In molecular modelling analysis, it has shown similarities between the RBDs of SARS-CoV and SARS-CoV-2 (also called S proteins), which are the most immunogenic part of the virus and probably bind the same ACE2 receptors in order to gain cell entry[ 7 , 8 ], thus suggesting that a similar pathogenic mechanism is involved in both viral infections. Interestingly, ACE2 receptors are not only expressed on alveolar epithelial type II cells, which represent 83% of all ACE2-expressing cells, but also on heart, kidney, endothelium, and gut cells[ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, two phase II studies with pulmonal amitriptyline already reported with favorable results [42]. Nevertheless, clinical development of sphingosine inhalation itself is also underway at least [7] and could potentially garner a lot more attention soon, as sphingosine was very recently shown to prevent viral entry of SARS-CoV-2 [43].…”
Section: Discussionmentioning
confidence: 99%